But How Were They Made? More about Patterned Textiles in the Aegean Bronze Age - Agata Ulanowska (Fasciculi Archaeologiae Historicae)
This paper scrutinises the iconography of patterned textiles in Bronze Age Greece as a potential source of technical knowledge of the patterning and weaving techniques. The variety of patterns on costumes depicted in Xeste 3, Akrotiri, Thera is a case study, examined in close relation to the textile technology available at the time, evidence of archaeological textiles from Greece and Akrotiri, and experimental reconstructions of the depicted patterns in weaving. By analysing several specific features of the painted and woven patterns, a critical overview of the possible techniques of manufacturing patterned textiles is presented. It is argued that there is little possibility of identifying a specific technique of patterning or weaving, on the basis of the Aegean iconography. However, specific features of the painted patterns seem to imitate in a great detail the appearance of the woven patterns. Therefore, it is argued that the wall painters were generally aware of the technical details of actual textiles and that it was important for them to attain a veracity in the rendering of the patterns.